20-Year Trends in Detection Rates of Cardia Cancer via Endoscopic Surveillance in Tianjin, China: A Hospital-Based Study. (5th April 2022) - Wang, Rui; Wu, Xiaowei; Song, Yan; Lin, Rui; Zheng, Zhongqing; Jiang, Kui; Liu, Wentian
Abstract : Background . To analyze the time trends in cardia cancer detection rates using endoscopic surveillance from 1999 to 2019 in a high-volume Chinese hospital. Methods . In this retrospective, single-center study, data were collected from the Endoscopy Center of the Department of Gastroenterology, Tianjin Medical University General Hospital, from 1999 to 2019. Cases of cardia cancer (n = 1567 ) were extracted from a database of patients who underwent endoscopy. Clinical and epidemiological characteristics of patients with cardia cancer were analyzed, including sex, age, and proportion of early gastric cancer and degree of tumor differentiation. The joinpoint regression method was used to identify change points in incidence trends. Annual percent change (APC) values, with 95% confidence intervals (CI), were calculated for time periods before and after change points. Results . Of the 343942 patients who underwent endoscopy during 1999–2009, 1567 (4.6%) were identified with cardia cancer. The overall cardia adenocarcinoma detection rate decreased significantly from 1999 to 2004 (APC = − 37.3, 95% CI: -20.9, -6.4), followed by a relatively slower decline rate from 2004 to 2019 (APC = − 7.7, 95% CI: -4.4, -7.6). The crude rate of detection of early cardia cancer could not be determined by joinpoint analysis. Rates of detection reduced significantly in patients aged 60–69 and 70-79 years (APC = − 8.3, 95% CI: -9.8, -6.8 and APC = − 7.3, 95% CI: -8.8, -5.8, respectively). The detection rate in males decreased rapidly from 1999 to 2004 (APC = − 35.9, 95% CI: -18.2, 5.6, P < 0.05 ), while the decline rate was relatively slow from 2005 to 2019 (APC = − 6.9, 95% CI: -3.4, -6.1, P < 0.05 ). Among females, the detection rates also decreased from 1999 to 2004 (APC = − 21.2, 95% CI: -28.1, -13.7), but remained stable from 2007 to 2019 (APC = − 3.8, 95% CI: -7.9, -0.5). Detection of poorly differentiated cardia cancer also declined from 2009 to 2019 (APC = − 12.8, 95% CI: -15.3, -10.0). Conclusions . The detection rate of cardia cancer among gastric cancers has been stable from 2008 to 2019. The trend of detection rate of early cardia cancer showed no significant statistical meaning; hence, it remains necessary to carefully observe the cardia area during endoscopy examination.